Intangible assets and firm-level productivity - Dirk Crass; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Firms invest huge amounts into intangible assets. This paper explores to which extent different kinds of intangible assets are conducive to firm-level productivity. Our study contributes to the literature by simultaneously comparing productivity effects of innovative capital, human capital, branding capital and organizational capital and testing whether complementarity or substitutability exists between different intangible assets. Using panel data for the period 2006-2010, our econometric estimates confirm strong positive productivity effects of human capital and branding capital. Results for innovative capital are found to be mixed. While R&D has a strong positive impact on productivity, design & licences and patents show only weak productivity enhancing effects. The same holds for organizational capital. We furthermore detect several complementarities among different kind of intangible assets. Our results are robust to various parametric (OLS, FE) and non-parametric (Olley and Pakes, Levinsohn and Petrin) productivity estimation methods.
Keywords: O33; C23; J24; L22; 330; Intangible capital; productivity; R&D; marketing; firm-specific human capital; organizational capital; patents; trademarks